The Algerian Islamic Movement from Protest to Confrontation: A Study in Systemic Conflagrations - Berkouk, M’hand (Intellectual Discourse, 2013)
The current crisis in Algeria has brought to the forefront the various dimensions of the Islamic tendency in the country. These include the political, the intellectual, the educational and the insurrectional aspects. While analyzing the various dimensions of the movement, this paper focuses on the mainstream of the movement. This mainstreamis essentially non-violent and actively involved in the established political process. It strives to transform both state and society in line with the essential precepts of Islam. It is the assertion of this paper that Islamic resurgence in Algeria is primarily a cultural phenomenon that cannot be understood by using simple quantitative analytical models. Only a multi-dimensional perspective that has as its centre focus the civilization and cultural forces can ascertain all the parameters and dynamics of this movement.